Kedudukan dan Peranan Perempuan Mulih Daa dalam Keluarga dan Masyarakat di Desa Pakraman Padangsambian Kecamatan Denpasar Barat - Ayu Gatriyani, Ni Komang; Kebayantini, Ni Luh Nyoman; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT With regard to the influence of patrilinial culture embraced by the people of Bali in general. Therefore, the basically this research was conducted to find out the position and the role which actually received by mulih daa women in the origin family and also in the society, particularly in Desa Pakraman Padangsambian. As well as finding out about the impact that then caused the position and role of. The theory which was used in this research is the theory of Structural Functionalism of Robert Merton in particular three postulates which criticized by him. The concept of functional alternative, manifest and latent functions used in analyzing problems in this research. This research uses descriptive qualitative research methods. The collected data were obtained with the technique of deep interviews, observation, and documentation. Mulih daa women were selected as key informants in this study were determined by purposive technique. Results found is the mulih daa women in Padangsambian in the fact, there is in returned with the status of head of the family and there are incoming only as a family member, in which those who choose the status as head of the family more have a role in society rather than just being a member of the family. The impact caused is the firstly, positive impact, where with the return of mulih daa women to the origin family provides assistance and power in the terms of economy, and secondly, the negative impact is culture increasingly cornered the women in the scope of its social function, especially for those who has status as a member of the family. Keywords: mulih daa women, position and role, Desa Pakraman Padangsambian